Urinary B-cell-activating factor of the tumour necrosis factor family (BAFF) in systemic lupus erythematosus. (November 2018) - Vincent, F B; Kandane-Rathnayake, R; Hoi, A Y; Slavin, L; Godsell, J D; Kitching, A R; Harris, J; Nelson, C L; Jenkins, A J; Chrysostomou, A; Hibbs, M L; Kerr, P G; et al.
Introduction: We examined the clinical relevance of urinary concentrations of B-cell–activating factor of the tumour necrosis factor family (BAFF) and a proliferation-inducing ligand (APRIL) in systemic lupus erythematosus (SLE). Methods: We quantified urinary BAFF (uBAFF) by enzyme-linked immunosorbent assay in 85 SLE, 28 primary Sjögren syndrome (pSS), 40 immunoglobulin A nephropathy (IgAN) patients and 36 healthy controls (HCs). Urinary APRIL (uAPRIL) and monocyte chemoattractant protein 1 (uMCP-1) were also quantified. Overall and renal SLE disease activity were assessed using the Systemic Lupus Erythematosus Disease Activity Index 2000. Results: uBAFF was detected in 12% (10/85) of SLE patients, but was undetectable in HCs, IgAN and pSS patients. uBAFF was detectable in 28% (5/18) of SLE patients with active nephritis vs 5/67 (7%) of those without ( p = 0.03), and uBAFF was significantly higher in active renal patients ( p = 0.02) and more likely to be detected in patients with persistently active renal disease. In comparison, uAPRIL and uMCP-1 were detected in 32% (25/77) and 46% (22/48) of SLE patients, respectively. While no difference in proportion of samples with detectable uAPRIL was observed between SLE, HCs and IgAN patients, both uAPRIL and uMCP-1 were significantly detectable in higher proportions of patients with active renal disease. Conclusions: uBAFF was detectable in a small but a significant proportion of SLE patients but not in other groups tested, and was higher in SLE patients with active renal disease.